Manfaat Promosi Pada Minat Beli Konsumen Toko Budi Jaya Alfath - Dedeh Sartika; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty; Siti Sa’adah Akmaliyah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Toko Budi Jaya Alfath is a business in the furniture sector that produces self-produced household furniture. The main purpose of industrial visits is to gain practical knowledge and experience in the field, which cannot be obtained through reading or teaching in class. In addition, industrial visits can also provide an overview of the work environment and working conditions of certain industries so that they can help participants prepare to work in that industry. The method used is descriptive method with direct observation by conducting interviews with the owner's wife. The results of the visit show that the promotion process using digital media platforms such as social media has a significant influence on consumer buying interest, the promotion process can help increase sales. Based on the results of this study, it is suggested that Toko Budi Jaya Alfath continue to pay attention to the importance of the promotion process using digital media in ensuring fast sales and increased sales.